The Correlation of Mathematics Ability and Chemistry Analysis Ability to Improve Student Learning Outcomes in Buffer Solution - Panggabean, Freddy Tua Musa; Fitria, Riska; Sutiani, Ani; Purba, Jamalum; Isnaini, Muhammad (J-PEK (Jurnal Pembelajaran Kimia), 2023)
This study aims to determine the linear and significant relationship between mathematical ability and chemistry learning results; chemical analytical abilities and learning result: association between students' chemistry learning outcomes and mathematical skills and chemical analysis abilities. This type of research is causal research with a quasi-experimental research design. Students in this study were given tests in the form of mathematical ability instruments, chemical analysis abilities, and buffer solution tests. This study found a linear and significant relationship between mathematical ability and students' learning outcomes, a linear and meaningful relationship between chemistry analysis ability and students' learning outcomes, and a significant relationship between mathematical knowledge and chemistry ability.